Producer participation in livestock systems research: Experience with on farm research among settled Fulani agropastoralists in central Nigeria - Taylor-Powell, E.; Kaufmann, Ralph R. von (Kansas State University, 1986)
Discusses the experience of the subhumid zone program of ILCA implementing a participatory approach to livestock systems research.